CONTRIBUTION OF MANAGEMENT INFORMATION SYSTEMS IN IMPROVING CUSTOMER RELATIONSHIP MANAGEMENT (CRM) IN E-BUSINESS THROUGH E-COMMERCE SYSTEMS - Sri Wahdini; Doni Sutanto; Rayyan Firdaus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The development of information technology has driven a major transformation in the business world, especially through the use of e-commerce in carrying out e-business activities. One of the crucial elements in maintaining the competitiveness of digital companies is customer relationship management or Customer Relationship Management (CRM). This article discusses the contribution of Management Information Systems (MIS) in supporting and improving the effectiveness of CRM on e-commerce platforms. By integrating MIS, companies can manage customer data in real-time, analyze consumer behavior, and design more personalized and responsive marketing strategies. Through a qualitative descriptive approach, this article highlights how MIS plays a role in data-based decision making, improving customer service, and building long-term loyalty in the context of e-business. The results of the discussion show that the implementation of a structured and integrated MIS can provide significant added value to the CRM strategy, which ultimately has a positive impact on the growth and sustainability of digital businesses.